2022
DOI: 10.7554/elife.73980
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive translation in Mycobacterium tuberculosis

Abstract: Most bacterial ORFs are identified by automated prediction algorithms. However, these algorithms often fail to identify ORFs lacking canonical features such as a length of >50 codons or the presence of an upstream Shine-Dalgarno sequence. Here, we use ribosome profiling approaches to identify actively translated ORFs in Mycobacterium tuberculosis. Most of the ORFs we identify have not been previously described, indicating that the M. tuberculosis transcriptome is pervasively translated. The newly described … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 65 publications
7
51
0
Order By: Relevance
“…Our results further suggested that many of the identified leaders were coding, in line with previous findings (35,36), and indicating that conditional termination of transcription is in many cases linked to translation. While we did find some commonality between our proposed leader peptides and those recently reported by Smith et al (36) (i.e. 9 exact matches and 28 isoforms, Supplementary Table 7), it appears from the number of peptides that did not match, that the methods of Ribo-seq/Ribo-ret and Term-seq are complementary in identifying potentially translated, and perhaps in particular, regulatory uORFs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results further suggested that many of the identified leaders were coding, in line with previous findings (35,36), and indicating that conditional termination of transcription is in many cases linked to translation. While we did find some commonality between our proposed leader peptides and those recently reported by Smith et al (36) (i.e. 9 exact matches and 28 isoforms, Supplementary Table 7), it appears from the number of peptides that did not match, that the methods of Ribo-seq/Ribo-ret and Term-seq are complementary in identifying potentially translated, and perhaps in particular, regulatory uORFs.…”
Section: Discussionsupporting
confidence: 91%
“…While we did find some commonality between our proposed leader peptides and those recently reported by Smith et al . (36) (i.e. 9 exact matches and 28 isoforms, Supplementary Table 7), it appears from the number of peptides that did not match, that the methods of Ribo-seq/Ribo-ret and Term-seq are complementary in identifying potentially translated, and perhaps in particular, regulatory uORFs.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the identification of so-called “one-hit wonders,” several PSMs (independent observations of the same peptide sequence) should be required. As small proteins are often of lower abundance ( 81 , 93 ) and hence are expected to produce few MS-detectable peptides, researchers have analyzed multiple biological conditions to increase their odds of identification, and used proteases other than trypsin ( Table 1 ) that can add more spectral evidence to support novel small protein identification ( 12 , 35 , 60 ). It is important to note that the number of false positive identifications will also increase as the size of the MS data set increases ( 94 , 95 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 105 ). Ribo-seq data can also complement MS-based evidence ( 104 ), and are particularly well-suited for identification of protein start sites ( 6 , 93 , 106 ), which is more challenging with MS-based approaches. Fifteen out of 16 novel small proteins jointly implied by Ribo-seq data and predicted by sPepFinder ( 107 ) in Salmonella enterica serovar Typhimurium were validated by MS, highlighting the complementarity of MS and Ribo-seq as methods to identify small proteins ( 104 ).…”
Section: Validation Of Novel Small Protein Candidatesmentioning
confidence: 99%
See 1 more Smart Citation